External Radiation Dose, Obesity, and Risk of Childhood Thyroid Cancer After the Fukushima Daiichi Nuclear Power Plant Accident: The Fukushima Health Management Survey. Issue 6 (November 2019) - Ohira, Tetsuya; Ohtsuru, Akira; Midorikawa, Sanae; Takahashi, Hideto; Yasumura, Seiji; Suzuki, Satoru; Matsuzuka, Takashi; Shimura, Hiroki; Ishikawa, Tetsuo; Sakai, Akira; Suzuki, Shinichi; Yamashita, Shunichi; et al.
Abstract : Background: The 2011 Great East Japan Earthquake led to a nuclear accident at Fukushima Daiichi Nuclear Power Plant. This study examines the associations of radiation dose and lifestyle factors with incidence of thyroid cancer in Fukushima. Methods: We designed a prospective study with 300, 473 participants aged 18 years or younger, who underwent thyroid examinations from October 2011. Follow-up surveys were conducted through June 2017, and 245, 530 participants (123, 480 men and 122, 050 women, 82% follow-up) received follow-up examinations. Fukushima Prefecture was divided into five areas based on individual external radiation dose. We calculated relative risks and 95% confidence intervals (CIs) for thyroid cancer in each area, with area of lowest dose as reference, using age-adjusted Poisson regression models. We also calculated risks associated with overweight and obesity. Results: The incidence per 100, 000 for Groups A (highest dose), B, C, D, and E (lowest dose) were 13.5, 19.2, 17.3, 9.0, and 8.3, respectively. Compared with Group E, the age-adjusted risks (95% CIs) were 1.62 (0.59, 4.47) for group A, 2.32 (0.86, 6.24) for group B, 2.21 (0.82, 5.94) for group C, and 1.02 (0.36, 2.86) for group D. Obesity was positively associated with thyroid cancer incidence; the multivariable-adjusted risk of thyroid cancer was 2.23 (1.01, 4.90) for obese individuals compared with nonobese individuals. Conclusion: Regional differences in radiation dose were not associated with increased risk of thyroid cancer among children in Fukushima within 4 to 6 years after the nuclear power plant accident. Obesity may be an important factor for further follow-up in Fukushima. Abstract : Supplemental Digital Content is available in the text.